2022
DOI: 10.1002/clt2.12143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti‐IL5 biological treatments on blood IgE levels in severe asthmatic patients: A real‐life multicentre study (BIONIGE)

Abstract: Background Mepolizumab and benralizumab are clinically effective biological treatments for severe eosinophilic asthmatic patients by hampering eosinophilic inflammation. The effects of these compound on the immunoglobulin (Ig)E T2 component are virtually unknown. Objectives To evaluate the change in total IgE levels at 4 ± 2 months after initiation of the mepolizumab (primary outcome) or benralizumab. When available, the changes of blood inflammatory cell counts, lung f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(91 reference statements)
0
2
0
1
Order By: Relevance
“…The results of our study are consistent with those of other studies [16][17][18][19][20]. In this study, we found that mepolizumab did not change IgE levels, which is in agreeance with the results of other studies [21,22]. This is because mepolizumab blocks IL-5 and may not affect other components of type 2 inflammation, such as IgE.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study are consistent with those of other studies [16][17][18][19][20]. In this study, we found that mepolizumab did not change IgE levels, which is in agreeance with the results of other studies [21,22]. This is because mepolizumab blocks IL-5 and may not affect other components of type 2 inflammation, such as IgE.…”
Section: Discussionsupporting
confidence: 93%
“…A recent multicentre real-life study enrolled patients treated with either mepolizumab (n ¼ 104) or benralizumab (n ¼ 82) for a mean of 3 months. 105 Benralizumab led to a significantly greater reduction in the BEC and basophil count than did mepolizumab, but the latter did not significantly change the total blood IgE concentration, unlike benralizumab (À35%, P < 0.001). This study provided further information on the different MoAs of anti-IL-5/IL-5R treatments.…”
Section: Benralizumabmentioning
confidence: 81%
“…In this regard, we have seen that some RWE studies are beginning to provide interesting evidence. [99][100][101][102][103][104][105][106][107][108] In the context of national and international registries and large databases, RWE studies can go beyond one of their most significant limitations, which is the low number of patients examined. 117,118 Big data obtained from networks and registers will also allow us to define alternative treatment schemes and dosages, but it is currently necessary to refer to those available.…”
Section: Complementary Results Between Clinical Trials and Real-life ...mentioning
confidence: 99%
“…In contrast, Mepolizumab demonstrated a marginal effect on basophils, consistent with our reported experience. The authors conclude that these results are due to the specific mechanisms of action of the different anti-IL5 treatments evaluated [ 55 ]. In addition, in a recent clinical trial of Mepolizumab treatment in aspirin-exacerbated respiratory disease, the authors found that there was no difference in IgE and IgG4 levels in patients taking or not taking this biologic drug [ 56 ].…”
Section: Discussionmentioning
confidence: 99%